2021
DOI: 10.2196/18819
|View full text |Cite
|
Sign up to set email alerts
|

A Home-Based Mobile Health Intervention to Replace Sedentary Time With Light Physical Activity in Older Cancer Survivors: Randomized Controlled Pilot Trial

Abstract: Background Older cancer survivors are at risk of the development or worsening of both age- and treatment-related morbidity. Sedentary behavior increases the risk of or exacerbates these chronic conditions. Light-intensity physical activity (LPA) is more common in older adults and is associated with better health and well-being. Thus, replacing sedentary time with LPA may provide a more successful strategy to reduce sedentary time and increase physical activity. Obj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 113 publications
2
20
0
Order By: Relevance
“…Secondary outcomes included trends in V and F consumption, physical activity, and HRQOL. The processing of the activPAL data to calculate time spent engaged in physical activities and sedentary activities has been previously described [ 47 ]. All activPAL variables were standardized to a 15-h day to limit the effect of within and between-person variability in awake/wear time.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes included trends in V and F consumption, physical activity, and HRQOL. The processing of the activPAL data to calculate time spent engaged in physical activities and sedentary activities has been previously described [ 47 ]. All activPAL variables were standardized to a 15-h day to limit the effect of within and between-person variability in awake/wear time.…”
Section: Methodsmentioning
confidence: 99%
“…We asked participants what types of technologies they used, the support they would need to use a WAT, and interest in this type of project. Based on a previous study by the principle investigator with older cancer survivors in urban, clinic-based setting in NM [20], we were interested specifically in Fitbit for the future intervention. We passed around a Fitbit Alta HR for participants to examine and showed them screenshots of the app.…”
Section: Identifying Locations and Recruitmentmentioning
confidence: 99%
“…Mobile health (mHealth) technologies, including consumer wearable activity trackers (WATs) and companion smartphone apps, have great promise in overcoming the limitations of in-person interventions to increase physical activity and reduce sedentary behaviors in older cancer survivors [20]. Studies revealed that WATs can provide behavioral modification strategies including self-monitoring, feedback, and goal setting, and that they are associated with behavior change in different populations [21][22][23], including cancer survivors [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 , 53 Similar to other physical activity interventions, depending on inclusion criteria, such as baseline activity levels, LIPA RCTs may struggle to actually increase LIPA. 53 …”
Section: Introductionmentioning
confidence: 99%